Перспективи формування соціального капіталу мезоекономічного рівня національної економіки - Малаховський, Ю. В.; Коваленко, С. В.; Кансо, А.; Malakhovskyi, Yu.; Kovalenko, S.; Canso, A.; Малаховский, Ю. В. (ЦНТУ, 2020)
Дослідження присвячено перспективам формування соціального капіталу національної економіки (СКНЕ) як продуктивної цінності активу інтерперсональних та міжгрупових мережевих зв’язків, що реалізуються у процесі виробництва узгоджених результатів суспільної діяльності. Особливу увагу приділено розрізненню ключових ознак СК на відміну від інших форм капітальних активів виробництва. Наводиться порівняльна матриця ідентифікації відмінностей, що властиві різним формам капіталу: за критеріями особливостей формування та втілення, природної сутності, ступеня поширення, здатності до відчуження, особливостей інвестування, інфляційного дисконтування у процесі споживання, рівня участі у процесі формування “ланцюгів” вартості товарів та послуг, здатності до ліквідності та конвертування, особливостей методів оцінювання. Досліджуються характерні чинники трансформаційного перетворення структурального, реляційного та когнітивного елементів СКНЕ з точки зору обставин та вимог формування постіндустріальної, постінформаційної, мережевої, гуманомічної, поведінкової економіки заощадливого та колективного користування суспільними благами. The purpose of the publication is to formulate theoretic and methodological provisions on the prospects for the development of social capital of localized post-industrial scientific and educational-production clusters that embody the idea of dynamic formation of innovatively oriented ecosystems of the national economy. The research is devoted to the prospects of forming the social capital of the national economy (SKNE) as a productive value of interpersonal and intergroup network connections implemented in the production of thoughtful and coordinated results of social activities. Particular attention is paid to the distinction of key features of SKNE, unlike other forms of capital assets in the production of goods and services. The comparative matrix of identification of differences inherent in different forms of capital, according to the criteria of features of formation and implementation, natural essence, degree of distribution, ability to alienate, features of investment, inflation discounting in the process of consumption, level of participation in the formation of “chains” of value of goods and services, ability to liquidity and conversion, features of valuation methods are given. The characteristic factors of transformation of structural, relational and cognitive elements of SKNE in terms of circumstances and requirements of formation of post-industrial, post-information, network, humanomic, behavioral economy of saving and collective use of public goods are investigated. Fully the requirements of the innoving mechanism of regulation of SKNE meets the incorporation to the tools for the implementation of goals and objectives of its development of means of forecasting the future state, structure, prospects for increasing the cost of elements. This provides an opportunity to increase SKNE on the basis of Foresight procedures for analyzing the impact of these factors, formulating and modernizing the mission of forecasting inclusive social capital, a comprehensive specification of the regulatory sector, taking into account macroeconomic development scenarios. The prospects for further research are seen in the implementation of imitation verbal models of social capital adapted to the needs of the different level of national economy: microeconomic – “Individual and egocentric network”, mesoeconomic – “Sociocentric Network”, macroeconomic – “Civil Society”. Исследование посвящено перспективам формирования социального капитала национальной экономики (СКНЭ) как производительной ценности межличностных и межгрупповых сетевых связей, реализуемых при производстве скоординированных результатов общественной деятельности. Особое внимание уделяется выявлению ключевых отличий СКНЭ от других форм капитальных активов производства. Приводится сравнительная матрица отличий, присущих различным формам капитала: в соответствии с критериями особенностей формирования и реализации, сущности, степени распространения, способности к отчуждению, особенностей инвестирования, инфляционного дисконтирования в процессе потребления, уровня участия в формировании “цепочек” стоимости товаров и услуг, склонности к ликвидности и конверсии, особенностей методов оценивания. Исследуются характерные факторы трансформационных преобразований структурных, реляционных и когнитивных элементов СКНЭ с точки зрения обстоятельств и требований формирования постиндустриальной, постинформационной, сетевой, гуманомической, поведенческой экономики коллективного использования общественных благ.
Prospects for the Formation of Social Capital of the Mesoeconomic Level of the National Economy
Перспективы формирования социального капитала мезоэкономического уровня национальной экономики
Keywords: соціальний капітал; мезоекономічний рівень національної економіки; планування та прогнозування; social capital; mesoeconomic level of the national economy; planning and forecasting; социальный капитал; мезоэкономический уровень национальной экономики; планирование и прогнозирование